STRATEGI PENGEMBANGAN WISATA DANAU TIMBANG BUNGA PENGANTIN OLEH BUMDES AUR KUNING DESA SUNGAI SORIK KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI TAHUN 2018 – 2020 - Ega Kumalasari; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tourism development is one way or effort to develop and advance a tourist attraction to make it better and more attractive both in terms of place and in terms of the objects in it. Tourism development is one component of national development which has the aim of developing an area. In encouraging village development and optimizing village assets, the Regency Government gives authority to the Village Government to manage its area independently, one of which is through economic institutions at the village level, namely Village Owned Enterprises (BUMDes).The aims of this study were to (1) describe the strategy of BUMDes Aur Kuning in developing Timbang Bunga Bride lake tourism in Sungai Sorik Village, (2) to find out the inhibiting factors for BUMDes Aur Kuning in developing Timbang Bunga Bride lake tourism in Sungai Sorik Village. This study uses a qualitative approach with a descriptive method. The location of this research was conducted in BUMDes Aur Kuning Sungai Sorik Village and data collection techniques were carried out by interview and documentation.The results of the study concluded that the strategy of BUMDes Aur Kuning in developing Timbang Bunga Bridal lake tourism in Sungai Sorik Village consisted of several strategies, namely technology strategies, innovation strategies, and operating strategies. However, in the implementation of this strategy, not everything is running optimally. There are several things that are inhibiting factors for BUMDes Aur Kuning in the development of Timbang Bunga Bridal lake tourism, namely the lack of tourist support facilities, lack of public awareness of the potential of village tourism, and the lack of third parties in supporting the development of tourism objects. Keywords: Strategy, Tourism Development, BUMDes